2018
DOI: 10.1007/s10980-018-0687-z
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics of the foundational salt marsh plant species black needlerush (Juncus roemerianus Scheele) across the northeastern Gulf of Mexico

Abstract: Context Common species important for ecosystem restoration stand to lose as much genetic diversity from anthropogenic habitat fragmentation and climate change as rare species, but are rarely studied. Salt marshes, valuable ecosystems in widespread decline due to human development, are dominated by the foundational plant species black needlerush (Juncus roemerianus Scheele) in the northeastern Gulf of Mexico.Objectives We assessed genetic patterns in J. roemerianus by measuring genetic and genotypic diversity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 84 publications
(115 reference statements)
2
21
0
Order By: Relevance
“…Genetic variation among keystone marsh species has been noted to affect ecosystem properties (Seliskar et al 2002). Zerebecki et al (2017) found that intraspecific variation in the salt marsh foundation species Spartina alterniflora affected plant-plant and plant-herbivore interactions, and Tumas et al (2018) noted the importance of genotypic diversity in preserving the adaptive potential of species following wetland restoration. Additional consequences of high genetic diversity in wetlands include the promotion of species coexistence (Vellend 2006), resiliency to disturbance (Brewer and Bertness 1996;Hughes and Stachowicz 2011), increased productivity and nutrient retention (Zedler 2005;Reynolds et al 2012), increased seed production (Sweetman et al 2013), and altered species interactions (Proffitt et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation among keystone marsh species has been noted to affect ecosystem properties (Seliskar et al 2002). Zerebecki et al (2017) found that intraspecific variation in the salt marsh foundation species Spartina alterniflora affected plant-plant and plant-herbivore interactions, and Tumas et al (2018) noted the importance of genotypic diversity in preserving the adaptive potential of species following wetland restoration. Additional consequences of high genetic diversity in wetlands include the promotion of species coexistence (Vellend 2006), resiliency to disturbance (Brewer and Bertness 1996;Hughes and Stachowicz 2011), increased productivity and nutrient retention (Zedler 2005;Reynolds et al 2012), increased seed production (Sweetman et al 2013), and altered species interactions (Proffitt et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The only genetic study on J. roemerianus to date examined clonal and genetic diversity across ten sites in the northeastern Gulf of Mexico from eastern Mississippi to the western panhandle of Florida (Tumas et al 2018). As reported for other clonal plant species (Ellstrand and Roose 1987;Silvertown 2008;Gabrielsen and Brochmann 1998;Lloyd et al 2011;Pleuss and Stocklin 2004), clonal and genetic diversity were higher than expected based on the existing life history literature with an average genotypic diversity of 0.54 and average observed heterozygosity of 0.58 across the ten sites.…”
Section: Introductionmentioning
confidence: 83%
“…1). Ten sites were sampled in the Gulf of Mexico as part of another study (Tumas et al 2018), two of which (GB and AP) are National Estuarine Research Reserves (NERR). A set of 304 samples was collected from Grand Bay NERR (GB) in January and March 2015, and a set of 32 samples was collected from Apalachicola NERR (AP) in May 2015 and March 2016.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-connected vegetation patch receives more dispersers and also provides more propagules (Taylor et al, 1993). In addition, connectivity allows species moving in the landscape to collect resources, colonize new habitats and help maintain genetic diversity through the dispersion of pollen and seeds (Tumas et al, 2018). These ecological processes can be affected by the lack of connectivity, risking the permanence of plant populations in a landscape (Santos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%